Uzbek Traditional Puppet Game and Oral Drama - Zokirova Dildorakhon Bakhtiyorjon qizi (Researchparks Publishing, 2022)
this article talks about the emergence and development of the art of the puppet theater in the history of the Uzbek traditional theater, as well as scientific research conducted during the study of the sphere.